2009
DOI: 10.1002/pca.1176
|View full text |Cite
|
Sign up to set email alerts
|

A validated spectrophotometric method for quantification of prenylated flavanones in pacific propolis from Taiwan

Abstract: The proposed spectrophotometric procedure is useful for routine analyses of Macaranga-type propolis, because of its simplicity, repeatability and acceptable accuracy. Its application to a number of commercial samples could be used as a basis for standardisation and quality control of Pacific propolis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 20 publications
1
40
0
1
Order By: Relevance
“…Dimov et al (1992) correlated the antibacterial activity of propolis with the presence of flavonoids; and Farnesi et al (2009) reported that the bactericidal effect of these compounds on the metabolic disturbance of ion channels due to paired phosphorylation / dephosphorylation reactions. The antimicrobial activity is also attributed to phenolic acids: ferulic, caffeic and cumaric, bioactive compounds found in propolis samples by Popova et al (2010). The presence of phenolic compounds in the samples of propolis explain their antimicrobial activity, which is supported by Marcucci (1995), who reported that caffeic acid, as well as benzoic acid and cinnamic acid act on the microbial membrane, causing structural damage to the cells.…”
Section: Antibacterial Activitysupporting
confidence: 55%
See 1 more Smart Citation
“…Dimov et al (1992) correlated the antibacterial activity of propolis with the presence of flavonoids; and Farnesi et al (2009) reported that the bactericidal effect of these compounds on the metabolic disturbance of ion channels due to paired phosphorylation / dephosphorylation reactions. The antimicrobial activity is also attributed to phenolic acids: ferulic, caffeic and cumaric, bioactive compounds found in propolis samples by Popova et al (2010). The presence of phenolic compounds in the samples of propolis explain their antimicrobial activity, which is supported by Marcucci (1995), who reported that caffeic acid, as well as benzoic acid and cinnamic acid act on the microbial membrane, causing structural damage to the cells.…”
Section: Antibacterial Activitysupporting
confidence: 55%
“…The chemical composition of propolis is highly variable and complex due to the biodiversity of the vegetation of each region visited by bees (Mohammadzadeh et al, 2007). However, even within the same country, the propolis composition may be qualitatively and quantitatively different depending on the region and time of collection (Koo, 1999), which makes it difficult for a universal standardization of their solutions (Popova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Propolis chemical composition depends on the phytogeographic characteristics of the site of collection, since bees choose different plants as source of propolis in different habitats (Popova et al, 2010a). This aspect difficults propolis standardization, and different solvents (ethanol, methanol and water) may extract different compounds, influencing its activity (Cunha et al, 2004).…”
Section: Propolis and Propolis Extracts Used In Biological Experimentmentioning
confidence: 99%
“…This process is going on, e.g. the recently proposed procedure for spectrophotometric quantification of total flavanones in Pacific type (Macaranga) propolis (Popova et al, 2010a). Quantification of individual constituents is not necessary at the initial stages of the studies.…”
Section: Propolis and Propolis Extracts Used In Biological Experimentmentioning
confidence: 99%
“…It is one of the world's most popular health foods. In Taiwan, ten propolins (A-J) of the active components were isolated and characterized from Taiwanese green propolis (TGP) (Chen et al, 2003(Chen et al, , 2004a(Chen et al, ,b, 2007Weng et al, 2007;Chen et al, 2008;Popova et al, 2010). TGP has proven to be a powerful antioxidant with anticancer properties.…”
Section: Introductionmentioning
confidence: 99%